The Influence of Brand Reputation and Brand Familiarity on Purchase Intention: A Study of the Wuling Electric Car Brand - Aldevian Risyad Pratama; Nurliya Apriyana (Manunggal Halim Jaya, 2027)
The rapid growth of the electric vehicle market in Indonesia has intensified competition among automotive manufacturers, making brand-related factors increasingly important in influencing consumer purchase intention. This study aims to examine the influence of brand reputation and brand familiarity on purchase intention of Wuling electric vehicle. A quantitative approach using a survey method was used. Data were collected from 149 respondents aged 17–55 years who reside in the Greater Jakarta area and expressed interest in Wuling electric vehicles. Data were analyzed using IBM SPSS Statistics through validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, and hypothesis testing. The results show that brand reputation has a positive but insignificant effect on purchase intention (p = 0.997), while brand familiarity has a positive and significant effect on purchase intention (p < 0.001). These findings indicate that consumer familiarity with the Wuling brand plays a more influential role than brand reputation in driving purchase intention. This study contributes to the marketing literature by emphasizing the importance of strengthening brand familiarity as a strategy to increase consumer purchase intentions in the Indonesian electric vehicle market.